(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2022)
This paper aims to identify an optimal investment strategy in cases of high-intensity R&D private micro entities. A game theory matrix is constructed using publicly available empirical data extracted from the financial statements of an R&D-intensive private micro-entity. The game theory matrix attempts to estimate the effect of the discretionary managerial choice to capitalise or expense the development cost of internally generated intangible assets; investors’ risk appetite could be affected by the capitalisation signalling. The investment strategies are classified based on their risk into three categories. High risk is represented by equity. Medium risk is represented by long-term debt, and low risk is represented by short-term debt. The game theory matrix results indicate that in similar situations, the dominant strategy is the medium-risk approach through long-term debt. This strategy must be confirmed by solving more game theory matrices based on similar R&D-intensive firms. However, it is an easily constructed advisory indicator for retail investors considering investing in unaudited small private entities. They could use it to identify an optimal investment strategy when uncertain of the genuine intangible asset prospects signaled via development cost capitalization.